Compliance of PPR 2008 : a study on LGED based on KPIs - Rahman, Md. Mahfuzar (BRAC University, 2013)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.